(Anty)przysłowia vel innowacje przysłowiowe w przestrzeni e-tekstów. Przyczynek do paremiologii w perspektywie tekstologicznej - Szutkowski, Tomasz (Studia Rossica Posnaniensia, 2019)
The article discusses proverb innovations in the aspect of textual criticism. On one hand, their functional specificity allows them to be still considered as fully-featured proverbs, on the other hand, it reveals an array of peculiarities related to modification and/or expansion of lexical composition of the output proverb, which is connected with identification of particular levels of meaning (literal, figurative and situational) by the receiver.